Families served during the first decade of the Supportive Services for Veteran Families program: a descriptive analysis - Renae Wilkinson; Katelyn N. G. Long; Katelyn N. G. Long; Richard G. Cowden; Richard G. Cowden; Howard K. Koh; Thomas H. Byrne; Thomas H. Byrne; Adrienne N. Melendez; Jack Tsai; Jack Tsai; Jack Tsai (Frontiers in Public Health, 2025)
Homelessness impacts entire families, with potential intergenerational consequences. Addressing family homelessness provides both immediate relief and long-term societal benefits. While various programs exist to mitigate homelessness, the United States (US) Department of Veterans Affairs’ (VA) Supportive Services for Veteran Families (SSVF) program offers a distinctive model for combating homelessness among veterans by supporting their families as well. We analyzed VA SSVF administrative data from 2014 to 2022, covering over 800,000 program entries from all SSVF beneficiaries in the US, to describe the sociodemographic profiles of SSVF veteran families—including children and adult family members of veterans. Families receiving SSVF assistance faced substantial economic and health-related challenges, including high unemployment, single-income dependency, and service-related disabilities. Children in these families represent a particularly vulnerable population, underscoring the need for targeted interventions to prevent long-term adverse outcomes. Our findings point to the role of SSVF in providing essential support for homeless veterans by also offering important services to their families. This broader approach offers lessons that may extend beyond the veteran community to address homelessness in individuals nationwide. Expanding coordinated, multi-agency approaches that build upon and modify the SSVF model could strengthen national efforts to reduce homelessness.